Systematic review: detoxification of free radicals from ionizing radiation with glutathione intake - Rachman, Rizaldy Fathur; Tualeka, Abdul Rohim; Ardyanto, Denny Y.; Jalaludin, Juliana; Ahsan, Julaikah; Rahmawati, Pudji; Ayu, Friska (ASR Research Institute, 2022)
Introduction: Radiation is the process of introducing energy that has a detrimental effect. If radiation hits the human body, radiation can ionize. If radiation penetrates body tissues, it can cause ionization and generate free radicals. Glutathione is one form of antioxidant-rich intake. Purpose: To determine the effect glutathione intake on the detoxification of free radicals from ionizing radiation. Methods: The inclusion criteria used are the population of rats, clinical trials, articles published between 2012 and 2022 and English. While the exclusion criteria used are title, abstract, free access and full text. Data sources are from PubMed, Scopus, Science Direct, and Google Scholar. Literature review writing starts from September 2022. Results: Based on a literature review conducted on 5 articles, it was found that total data using keywords the effect of free radical detoxification from ionizing radiation (n= 104) data focused on glutathione intake (n=96), searched based on exclusion criteria (n=44), search based on inclusion criteria (n=7), number of articles synthesized and analyzed (5). Conclusions: There is a direct effect of glutathione intake on the detoxification of free radicals from ionizing radiation. There is limited evidence so further research is needed on the effect of glutathione intake on free radical detoxification by testing the levels of free radicals and antioxidants in cells.